Rezension von: Lässing, Horst; Fritz, Gerhard, Unser Rems-Murr-Kreis - Kozlik, Andreas (Württembergisch Franken, 1995)
Horst Lässing und Gerhard Fritz, Unser Rems-Murr-Kreis, Stuttgart (Theiss) 1994. 111 S., zahlr. Abb.